Dragon hoops - Yang, Gene Luen; Pien, Lark; Meyers, Rianne; Yang, Kolbe (New York : First Second, 2020)
Gene Luen Yang turns the spotlight on his life, his family, and the high school where he teaches especially the high school's basketball team, the Dragons.
Includes bibliographical references.
Keywords: Yang, Gene Luen; Basketball -- Comic books, strips, etc -- Tournaments -- California; Basketball -- Comic books, strips, etc; Basketball teams -- Comic books, strips, etc -- California; Chinese Americans -- Comic books, strips, etc; High schools -- Comic books, strips, etc -- California; High school teachers -- Comic books, strips, etc; Cartoonists -- Comic books, strips, etc; Yang, Gene Luen -- Cartoons and comics; Basketball -- Cartoons and comics. -- Tournaments; Basketball -- Cartoons and comics; Basketball teams -- Cartoons and comics; Chinese Americans -- Cartoons and comics; High schools -- Cartoons and comics; High school teachers -- Cartoons and comics; Cartoonists -- Cartoons and comics; Cartoons and comics; Oakland (Calif.) -- Comic books, strips, etc; Oakland (Calif.) -- Cartoons and comics; Autobiographical comics; Graphic novels; Comics (Graphic works)